(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Ability of biomarkers to accurately assess a patient’s disease severity and prognosis in emergency department can predict the aggressiveness of the treatment given in due course of time. Serum procalcitonin (PCT) has been used as a marker of bacterial sepsis in critically ill patients and prediction of outcome after major trauma Systemic inflammation in response to infection, tissue injury or inflammatory disease down regulates the production of few proteins including the albumin. Aim: To compare the utility of serum albumin as a prognostic marker with serum PCT in patients admitted in the emergency department. Materials and Methods: This retrospective evaluation of data on patients admitted in emergency department of a government-run Tertiary Care Centre in Western Uttar Pradesh over a period of two months was performed to establish a relationship between their serum albumin levels and serum PCT levels. The analysis was performed on the data of 75 emergency admitted patients after considering the exclusion criteria and availability of serum albumin and PCT reports of patients. Patients were divided into two groups based on whether the serum PCT value was < 0.5 ng/mL or ≥ 2 ng/mL. The mean values of serum albumin were compared in the subgroups of patients defined by the level of serum PCT by unpaired t-test and spearman rank correlation coefficient was calculated to establish the correlation between serum albumin and serum PCT levels. Results: A large number (88%) of the patients had hypoalbuminaemia with mean albumin level being 2.8 ± 0.6 g/dL. About 44% of patients had serum PCT level less than 0.5ng/mL, 24% had serum PCT level ≥ 0.5ng/mL to < 2ng/mL and 32 % patients had serum PCT level ≥ 2ng/mL. The mean value of serum albumin was lower among those with high serum PCT (> 2 ng/dL) as compared to those with Serum PCT value less than 0.5 ng/dL, that was significant statistically (p value < 0.001). The correlation coefficient between serum PCT and serum albumin levels was -0.442 which shows that both the parameters are negatively correlated and this finding was statistically significant. Conclusion: The significant difference was observed between mean serum albumin values in the two groups based on whether the serum PCT value was less than 0.5 ng/mL and equal to or more than 2 ng/mL. The serum albumin levels of the patients were negatively correlated with their serum PCT levels which was statistically significant. So this study concluded that the low serum albumin levels can also predict the severity of systemic inflammation.